Internalisasi Pendidikan Karakter Melalui Pelaksanaan Dharmagita Pada Sekaa Teruna - I Ketut Sudarsana; G. A. P Yuni Arwani (Jayapangus Press, 2018)
Hinduism in everyday life can not be kept away with the name yajńa. Yajna is a sincere sacred offering consisting of five yajńa or panca yajńa. In practice yajńa is supported by banten, saint, panca gita. Taste, pride, calm, peace can also be felt in chanting dharmagita. With the decreasing interest of adolescents especially in learning dharmagita, then family and coach can increase dharmagita training to adolescent in particular. The role of informal education is needed to internalize the values of Hindu characters to sekeha teruna teruni through the implementation of dharmagita.